Description of Protosticta hopkinsi sp. nov. from the Bidoup Nui Ba National Park, the Central Highlands of Vietnam (Odonata: Zygoptera: Platystictidae) - Phan, Quoc Toan; Mai, Nguyen Thi Phuong; Son, Le Van (Zootaxa, 2026)
Protosticta hopkinsi sp. nov. is described from the Central Highlands of Vietnam (Holotype ♂: Vietnam, Lam Dong Province, Lac Duong District, Thien Thai waterfall, 12.14472°N, 108.52944°E, alt. 1,559 m a.s.l., 29 April 2025, Zoological Collection of Duy Tan University). The new species can be easily distinguished from all other species in the Protosticta trilobata group by the combination of the yellow stripe on dorsal synthorax of male and female, and the shape of the apical part of the paraprocts.